Geo-Chicago 2016 2016
DOI: 10.1061/9780784480120.062
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Life Cycle Benefits of Recycled Material in Road Construction

Abstract: Executive SummaryThere is interest in determining and validating the environmental and economic benefits of incorporating recycled materials into road construction using life cycle assessments (LCA) and life cycle cost analysis (LCCA) tools. However, the process of collecting the necessary data for LCAs and LCCAs from departments of transportations (DOTs) and road construction contractors is not well defined. This thesis provides a study of real-time data collection to compare with the results of pre-construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Advantages of using PaLATE 2.0 include its ease of access and the possibility of modifying its materials and process databases, which take local conditions into account. Further details concerning PaLATE 2.0 can be found in Horvath [34] and Bloom [35]. PaLATE 2.0 evaluates the following environmental impacts: Human toxicity potential (noncancer), accounting for adverse health effects on human beings caused by the intake of toxic substances.…”
Section: Environmental Impacts and Cost Analysesmentioning
confidence: 99%
“…Advantages of using PaLATE 2.0 include its ease of access and the possibility of modifying its materials and process databases, which take local conditions into account. Further details concerning PaLATE 2.0 can be found in Horvath [34] and Bloom [35]. PaLATE 2.0 evaluates the following environmental impacts: Human toxicity potential (noncancer), accounting for adverse health effects on human beings caused by the intake of toxic substances.…”
Section: Environmental Impacts and Cost Analysesmentioning
confidence: 99%
“…RAP, RCA, and fly ash were used most extensively across the states, while Illinois also tracked steel slag, by-product lime, glass beads, microsilica, dowel bars, rebar, and welded wire reinforcement. The study found the average environmental impacts savings of using recycled material in highway construction instead of virgin resources to be between 80-97% (Bloom et al, 2016). As DOTs continue to increase the use of recycled material for construction projects, a tool to track source material and quantities for each project would be beneficial and useful for many applications such as life cycle assessment.…”
Section: Department Of Transportation Use Of Recycled Materialsmentioning
confidence: 99%
“…Application for the reuse of the byproducts include aggregate in pavement, structural fill, road embankments, and manufactured consumer products. Examples of some of the most commonly used nonhazardous industrial byproducts in construction applications include recycled concrete aggregate (RCA), recycled asphalt pavement (RAP), recycled asphalt shingles (RAS), coal fly ash, blast furnace slag, and rubber (Bloom et al, 2016). There have been many efforts to characterize the engineering properties of these materials, test the materials in varied applications, raise awareness about the potential usefulness of these materials, and market the byproducts as commodities.…”
Section: Introductionmentioning
confidence: 99%
“…This can help reducing the demand for virgin aggregates and bitumen as well as mitigating their overall cost [5,6]. Although reclaimed asphalt is currently added to a new asphalt mixture up to 15-20% by weight due to technological limitations, the latest advances in asphalt plants, best practices and cutting-edge technologies demonstrate the possibility of increasing the amount of reclaimed asphalt in the production of AMs to high (over 40%) or to very high (up to 100%) RAP content [7][8][9][10][11]; thus further enhancing the circularity scheme and reducing the impacts [12][13][14]. The encouragement of its use reflects the worldwide trend to face the existing environmental issues by trying to increase the efficient use of resources and reduce carbon emission.…”
Section: Introductionmentioning
confidence: 99%